LEVELS OF COMMUNITY PARTICIPATION IN THE VILLAGE INFRASTRUCTURE DEVELOPMENT PROGRAM IN BINUANG VILLAGE, BALUSU DISTRICT, BARRU DISTRICT - Safaruddin; Muliati; Lubis, Iksan Adiputra (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal